Application of the Turning Band Method (TBM) on Reinforced Concrete Beams without Shear Reinforcement Using the Mazars Damage Model - Shinta Fatina Elba; Nuraziz Handika (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2026)
Reinforced concrete beams without shear reinforcement may exhibit different failure modes among specimens, even when they possess identical geometric dimensions and mechanical properties. This variation is associated with the intrinsic heterogeneity of concrete, which results in spatial variability in its mechanical characteristics. This study examines the numerical behavior of reinforced concrete beams without shear reinforcement using a random field approach implemented through the Turning Band Method (TBM) coupled with the Mazars damage model and validates the numerical predictions against experimental results employed as the reference. The numerical simulations were conducted on beams with a shear span-to-depth ratio of 4.6 using five random field realizations in the Finite Element (FE) software CAST3M version 24.1. A mesh size of 10 mm and correlation length of 30 mm were adopted throughout the analysis. The findings indicate that integrating the TBM with the Mazars damage model effectively captures the spatial variability of the concrete tensile strength, leading to distinct force–displacement responses and crack propagation patterns among realizations that cannot be reproduced by conventional homogeneous models. However, discrepancies remained in peak displacement, and the numerical model tended to produce more distributed damage zones than those observed experimentally, owing in part to the Perfect Interface assumption adopted in the numerical model.